Efectividad de Ketamina comparada con placebo en pacientes con anestesia general que desarrollan hiperalgesia inducida por opioides - Namuche Quiñones, Juan Luis (2022)
Opioids are highly effective analgesics and as such form the basis of pain management after surgery(1). Although they act as analgesics, there is evidence that opioids cause hyperalgesia(2). Opioid-Induced Hyperalgesia (OHI) is defined as a state of nociceptive sensitization originating after exposure to opioids that leads to an increased perception of pain(3). The factors associated with the development of hyperalgesia secondary to the use of opioids are not fully defined; however, high doses, prolonged infusion time or abrupt changes in the rate of infusion or in the infusion concentration of said opioid have been included(6). Taking into account that the main objectives consist of reducing the dose of opioids as much as possible and supplementation with NMDA receptor modulators (N-methyl-D-aspartate) such as ketamine. There is evidence, that theintravenous ketamine at subanesthetic doses associated with general anesthesia reduces postoperative pain and opioid requirements(9).